Hodnocení finanční situace podniku a návrhy na její zlepšení - Mandelíček, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce je zaměřena na zhodnocení finanční situace firmy VAŠSTAV s.r.o. v letech 2013-2017 metodami finanční analýzy. Práce je rozdělena do tří částí. První část je teoretická a jsou v ní popisovány definice pojmů či metod spjatých s finanční analýzou. Druhá část se zabývá finanční analýzou současného stavu dané společnosti. Poslední část se zaměřuje na návrhy pro zlepšení finanční situace daného podniku pro následující roky.

Bachelor thesis is focused on the evaluation of the financial situation of a company VAŠSTAV s.r.o. within the years 2013-2017 using methods of financial analysis. The work is divided into three parts. First part is theoretical and there are descibed tools of a financial analysis that will be used in thesis. Second part is analysis of current state of the company. Last part is focused on proposals to improve the financial situation of the company for the coming years.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: finanční analýza; horizontální analýza; vertikální analýza; výkaz zisků a ztrát; rentabilita; zadluženost; likvidita; financial analysis; horizontal analysis; vertical analysis; profit and loss statement; profitability; indebtednes; liquidity